Analisis Asphalt Concrete Wearing Course (AC-WC) Modifikasi Dengan Penambahan Wood Ash Dan Styrofoam Expanded Polystyrene (EPS) Untuk Perkerasan Jalan - Pradita Setya Ningtyias; Siti Fatimah; Rachmat Mudiyono (Journal of Engineering and Applied Technology, 2025)
This laboratory-based quantitative experimental study evaluated the performance of Asphalt Concrete Wearing Course (AC-WC) modified with wood ash as filler and Expanded Polystyrene (EPS) styrofoam as asphalt additive. The research verified the base binder through penetration testing, yielding an average penetration value of 69.4, confirming the use of 60/70 penetration grade asphalt. Asphalt content was validated using extraction testing, resulting in an average binder content of 5.80%, ensuring consistency between design and actual mixture composition. Marshall testing was conducted to assess mechanical and volumetric characteristics, including stability, flow, Marshall Quotient (MQ), VMA, VIM, and VFB. The results demonstrated that EPS dosage significantly influenced volumetric balance and load resistance within the mixture. Among the evaluated combinations using 4% wood ash and EPS levels of 0%, 0.5%, 1%, and 1.5%, the optimum performance was achieved at 1.5% EPS, which satisfied key Bina Marga 2018 Revision 2 requirements for VIM, VMA, VFB, stability, and flow. However, MQ values remained below specification for all mixtures, indicating limitations in stiffness–deformation ratio and the need for further optimization and durability testing.